A Rare Case of Hydatid Cyst in the Inguinal Area: A Case Report - A Dalili (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Hydatid disease is a common health problem in developing countries. The liver and lungs are the most common organs affected by this infection. Hydatid cyst is very rare in the inguinal area. The aim of this case report was to introduce a patient with multiple hydatid cysts in the right inguinal area who developed symptoms of inguinal hernia. CASE REPORT: The patient is a 92-year-old man who was referred to Imam Reza Hospital in Mashhad due to pain, swelling and redness in the right inguinal area. The patient s blood tests showed an increase in neutrophils, and a decrease in eosinophils, basophil and monocyte. Ultrasound examinations of the patient revealed right inguinal hernia and hydatid cysts in the liver, abdomen and pelvic cavity. Finally, the patient was operated with a diagnosis of incarcerated inguinal hernia. During the operation, multiple cysts were observed in the inguinal area; the cysts were removed and sent to pathology. Pathological findings confirmed the presence of hydatid cyst. After 2 days, the patient was discharged in relatively good general condition and with albendazole (400 mg) twice daily for 6 months. At the end of the treatment period, no signs of recurrence of hydatid cyst were observed in the patient. CONCLUSION: According to the cases reported in patients diagnosed with hydatid cyst with inguinal pain, the possibility of migration or hernia of hydatid cyst should be considered, because knowing its presence is useful for preoperative planning and reduction of complications.